If I ever get out of here - Gansworth, Eric L. (Scholastic Inc., 2015)
Seventh-grader Lewis "Shoe" Blake from the Tuscarora Reservation has a new friend, George Haddonfield from the local Air Force base, but in 1975 upstate New York there is a lot of tension and hatred between Native Americans and Whites--and Lewis is not sure that he can rely on friendship.